Prognostic factors of functional outcome after hip fracture surgery: a systematic review. (12th April 2018) - Sheehan, K J; Williamson, L; Alexander, J; Filliter, C; Sobolev, B; Guy, P; Bearne, L M; Sackley, C
Abstract: Objective: this systematic review aimed to identify immutable and modifiable prognostic factors of functional outcomes and their proposed mechanism after hip fracture surgery. Design: systematic search of MEDLINE, Embase, CINAHL, PEDRO, OpenGrey and ClinicalTrials.gov for observational studies of prognostic factors of functional outcome after hip fracture among surgically treated adults with mean age of 65 years and older. Study selection, quality assessment, and data extraction were completed independently by two reviewers. The Quality in Prognosis Studies Tool was used for quality assessment and assigning a level of evidence to factors. Proposed mechanisms for reported associations were extracted from discussion sections. Results: from 33 studies of 9, 552 patients, we identified 25 prognostic factors of functional outcome after hip fracture surgery. We organised factors into groups: demographics, injury and comorbidities, body composition, complications, and acute care. We assigned two factors a weak evidence level—anaemia and cognition. We assigned Parkinson's disease an inconclusive evidence level. We could not assign an evidence level to the remaining 22 factors due to the high risk of bias across studies. Frailty was the proposed mechanism for the association between anaemia and functional outcome. Medication management, perceived potential, complications and time to mobility were proposed as mechanisms for the association between cognition and functional outcome. Conclusion: we identified one modifiable and one immutable prognostic factor for functional outcomes after hip fracture surgery. Future research may target patients with anaemia or cognitive impairment by intervening on the prognostic factor or the underlying mechanisms.